A glimpse into the application of the immunomodulatory effect of IL-2 in systemic lupus erythematosus - Xia, Xin; Qu, Rui (Frontiers in Medicine, 2025)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease, which is mainly caused by the imbalance of immune cells. Current treatment regimens predominately rely on corticosteroids and immunosuppressive agents, accompanied by various side effects. Interleukin-2 (IL-2) is deemed an important cytokine for innate immune cells and adaptive immune cells, especially for the promotion of Treg cells. By combining IL-2/IL-2R system with engineered T cell-based immunotherapies to enhance the therapeutic efficacy of engineered T cells shows its potential in autoimmune diseases. But the pleiotropy of IL-2 may cause simultaneous stimulation and systemic toxicity, limiting its therapeutic use. There is a growing focus on using IL-2 in combination strategies for synergistic immune enhancement. In this article, we review the IL-2/IL-2R signaling, including IL-2 dependent signaling and IL-2 independent signaling, and discuss its functions in regulation of different immune cells. In addition, we summarize major clinical application of low-dose IL-2 treatment in SLE with or without other agents, such as rapamycin, tocilizumab and rituximab, present the IL-2 variants and fusion proteins designed for SLE, and highlight the future trends for research on these cytokine-based immunotherapies. It will help to design further optimized IL-2-based therapy for SLE.